From Lean Value Stream to Circular Value Stream Architecture (CVSA): A Conceptual Framework for Sustainable and Regenerative Supply Chain Transformation - Adi Fitra; Nanang Susanto (JURNAL TEKNIK DAN SISTEM INDUSTRI, 2026)
This study proposes a novel conceptual framework called Circular Value Stream Architecture (CVSA) to extend the conventional role of Value Stream Mapping (VSM) from a process improvement tool into an integrated value architecture. The novelty lies in introducing a regenerative perspective that combines Flow Efficiency, Sustainability Creation, Resource Circularity, and Regenerative Feedback within a single conceptual structure. Existing studies have progressively incorporated sustainability, circularity, and system transformation perspectives into Lean and VSM; however, these developments remain fragmented and primarily additive, limiting their ability to establish an integrated value generation mechanism. To address this gap, this study employed a conceptual synthesis approach using a literature-derived dataset as the basis for concept extraction, concept clustering, relationship abstraction, and framework construction. No empirical testing, simulation, statistical validation, or bibliometric analysis was conducted because the objective was theory development. The proposed framework suggests that value should no longer be interpreted as a final operational outcome but as a continuously renewed process. Nevertheless, the framework remains conceptual and requires future research to develop measurement models, empirical validation, and implementation studies across different operational contexts.